REVIEW OF CONSTRUCTION MANAGEMENT AND ECONOMICS RESEARCH OUTPUTS IN NIGERIA: TOWARDS A SUSTAINABLE FUTURE - Obuks Augustine EJOHWOMU; Olalekan Shamsideen OSHODI (Journal of Construction Project Management and Innovation)
Construction related research holds the key to a sustainable future. This is because of the potential of research to improve practice. In order to identify the current state of knowledge in construction management and economics research. This article aims to unpack the question by evaluating three (3) decades of longitudinal data into construction management and economics research across seven (7) foremost Nigerian universities. A review of completed PhD studies was done to identify dominant research topics, methods and t rends over the study period. It is evident from qualitative analysis that 69.9% of the critical investigation focused on topics related to procurement/project per formance, maintenance, cost modelling/construction economics and human resource/productivity. Despite, a moving trend in the topics investigated. There was no evidence of critical research in the area of sustainability. Besides a call for paradigm shift in present day research activities, the concept of sustainability, which has become a dominant policy in the developed world, needs to be enshrined. In other words, there is a need to really examine the extent to which current policies and activities pertai ning to sustainability in the construction industry is been integrated into built environment plann ing and development in Nigeria